Current status of endovascular treatment for older adults with acute large vessel occlusion stroke in China: subgroup analysis of ANGEL act registry - Han, Bin; Sun, Dapeng; Raynald,; Jia, Baixue; Tong, Xu; Wang, Anxin; Mo, Dapeng; Gao, Feng; Ma, Ning; Miao, Zhongrong (Frontiers in Neurology, 2023)
Background: Although endovascular treatment (EVT) has become the standard treatment for acute large-vessel occlusion (LVO), its safety and efficacy in older adults have not been fully determined. The present study aimed to compare the safety and efficacy of EVT for acute LVO between younger (<80 years old) and older adults (>80 years old) in the Chinese population. Methods: Subjects were selected from the ANGEL-ACT registry (endovascular treatment key technique and emergency work flow improvement of acute ischemic stroke). The 90-day modified Rankin score (mRS), successful recanalization, procedure duration, number of passes, intracranial hemorrhage (ICH), and mortality within 90 days were compared after adjusting for confounders. Results: A total of 1691 patients, 1543 classified as young and 148 classified as older were included. We observed that young and older adults had a similar 90-day mRS distribution, successful recanalization, procedure duration, number of passes, ICH, and mortality within 90 days (all P > 0.05). The rate of 90-day mRS 0-3 was found to be higher in young patients than in older adults (39.9% vs. 56.5%, odds ratio = 0.64, 95% confidence interval = 0.44–0.94], P=0.022). Conclusion: We found that patients less than or greater than 80 years of age share similar clinical outcomes, without increasing the risk of ICH and mortality